Market competition, earnings management, and persistence in accounting profitability around the world - Healy, Paul; Serafeim, George; Srinivasan, Suraj; Yu, Gwen (Review of Accounting Studies, 2014)
We examine how cross-country differences in product, capital, and labor market competition, as well as earnings management affect mean reversion in accounting return on assets. Using a sample of 48,465 unique firms from 49 countries, we find that accounting returns mean revert faster in countries where there is more product and capital market competition, as predicted by economic theory. Country differences in labor market competition and earnings management are also related to mean reversion in accounting returns—but the relation varies with firm performance. Country labor competition increases mean reversion when unexpected returns are positive but slows it when unexpected returns are negative. Accounting returns in countries with higher earnings management mean revert more slowly for profitable firms and more rapidly for loss firms. Thus earnings management incentives to slow or speed up mean reversion in accounting returns are accentuated in countries where there is a high propensity for earnings management. Overall, these findings suggest that country factors explain mean reversion in accounting returns and are therefore relevant for firm valuation.